Overview of Parents Anxiety Level on Online Learning During The Covid-19 Pandemic - Nur Hidayat; Andan Firmansyah; Syahdan Nurul Bayan; Yuyun Rahayu (Jurnal Vocational Nursing Sciences (VNUS), 2021)
Background: Corona virus disease has become a global pandemic. Coronavirus is a new name given by the World Health Organization to patients infected with the virus. Impact of the very fast spread of the COVID-19 virus, so the government implemented an online learning policy in order to prevent the spread of COVID-19 transmission to school residents in particular and to the community. Objective: This study aims to determine the level of parental anxiety in online learning during the COVID-19 pandemic. The rapid spread causes infected patients to self-isolate to break the chain of the spread of the COVID-19 virus. Method: The design used in this study is a quantitative descriptive method. The researcher intends to find out factually about the level of anxiety of parents towards online learning during the COVID-19 pandemic. The population taken from the results of proportional sampling is 52 people, with the results of sampling the parents of students at the Madrasah Tsanawiyah (MTS) level. The results of the study: The results of the description of the level of parental anxiety in online learning during the COVID-19 pandemic showed that 20 respondents had severe anxiety levels, as many as 20 people (37.7%) with their parents. Conclusion: The results of the study showed that the majority of parents experienced severe anxiety.